If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+3u=-9+9u
We move all terms to the left:
3+3u-(-9+9u)=0
We add all the numbers together, and all the variables
3u-(9u-9)+3=0
We get rid of parentheses
3u-9u+9+3=0
We add all the numbers together, and all the variables
-6u+12=0
We move all terms containing u to the left, all other terms to the right
-6u=-12
u=-12/-6
u=+2
| -7x+20=4x-50 | | 2(3v-3)-2(v+2)=6 | | 3+3u=-9+3u | | 2+3b=-14+7b | | -8-q=-2q | | -41+14x-12x=11 | | 3(5x-5)=5(3x+4) | | 5x+8=2x-x | | 10-5q=-7q-10 | | 12.6x-3.7=178 | | 167=105-w | | 4c+6=2c-10 | | 12x-14x-22=42 | | 3x+x+2x=-18 | | -6x-34=-4x+26 | | -2s+16=-4 | | -(3x+1)-5=25 | | 2(x+2)=100 | | -2/5=-1/2w-6/7 | | 3x+17=x-7 | | -8+y-36=1 | | -184-3x+14x=58 | | 6-(8m-20)=5m | | 2.1m+1.3m-4.6=2.2 | | 20y-y=-11 | | 8(m+6)-(-4+4m)=80 | | 6–2b=4 | | 1/4x+6=9 | | 6x.25+3=2x.25+3 | | -7+4t=-11 | | 14-5p=44 | | 3y+5=160 |